MANAGEMENT OF AN INVASIVE PLANT IN A MEDITERRANEAN PROTECTED AREA: THE EXPERIENCE OF Senecio deltoideus IN ITALY - Minuto, L.; Casazza, G.; Dagnino, D.; Guerrina, M.; Macrì, C.; Mariotti, M.G. (Annali di Botanica, 2021)
Biological invasions are one of the most serious threats to global biodiversity and ecosystem integrity. The problem is growing year by year and a large number of protected areas worldwide are today invaded by at least one exotic species. In this study, we tested the eco-friendly and cost-effective weeding control of Senecio deltoideus in a Regional Protected Area in the North Mediterranean region. During a two years experiment, four techniques compatible with the local laws on protected areas (natural-herbicide, flame-weeding, mulching and mowing) were applied five times a season on sixty plots, compared with fifteen untreated controls. All techniques were effective in reducing Senecio covering: after the first year the maximum covering was limited to 37.93% (flame weeding) with a mean value of 10%; after second year the covering was further reduced (17.02% max; 2% mean). Interestingly, during the second year all plots submitted to a one-year treatment showed an enduring control of S. deltoideus covering (40.73% max; 20% mean). Taking into account feasibility and their impact on the environment, the weeding control recommendable for S. deltoideus is mowing. In a long-time management strategy, the selected treatment could be applied every two years with a drastic reduction in costs for the manager of the protected area.